A preliminary report of the cost‐effectiveness of tooth replacement strategies for partially dentate elders. (8th March 2012) - McKenna, Gerald; Allen, P Finbarr; Woods, Noel; O'Mahony, Denis; DaMata, Cristiane; Cronin, Michael; Normand, Charles
Abstract : doi: 10.1111/j.1741‐2358.2012.00665.x A preliminary report of the cost‐effectiveness of tooth replacement strategies for partially dentate elders Objective: To compare the cost‐effectiveness of conventional treatment using partial dentures with functionally orientated treatment to replace missing teeth for partially dentate elders using a randomised controlled clinical trial. Background: In many countries, including the Republic of Ireland, the only publically funded treatment option offered to partially dentate older patients is a removable partial denture. However, evidence suggests that these removable prostheses are unpopular with patients and can potentially increase the risk of further dental disease and subsequent tooth loss. Materials and Methods: Fourty‐four partially dentate patients aged 65 years and older were recruited. Patients were randomly assigned to the two treatment arms of the study. The conventional treatment group received removable partial dentures to replace all missing natural teeth. The functionally orientated group was restored to a Shortened Dental Arch (SDA) of 10 occluding contacts using resin‐bonded bridgework (RBB). The costs associated with each treatment were recorded. Effectiveness was measured in terms of the impact on oral health‐related quality of life (OHRQoL) using OHIP‐14. Results: Both groups reported improvements in OHRQoL 1 month after completion of treatment. The conventional treatment group required 8.3 clinic visits as compared to 4.4 visits for the functionally orientated group. The mean total treatment time was 183 min 19 s for the conventional group vs. 124 min 8 s for the functionally orientated group. The average cost of treatment for the conventional group was 487.74 Euros compared to 356.20 Euros for the functional group. Conclusions: Functionally orientated treatment was more cost‐effective than conventional treatment in terms of treatment effect and opportunity costs to the patients' time.